An efficient DOA estimation technique for multi-user multi-path signals in TD-SCDMA systems - Li Ping'an (MAPE2005 : IEEE 2005 International Symposium on Microwave, Antenna, Propagation, and EMC Technologies for Wireless Communications : proceedings : August 8-12, 2005, Beijing, China, 2005)
An efficient method is presented for multi-path DOA estimation in TD-SCDMA systems. With a specific midamble assignment strategy, a DFT-based algorithm is used to obtain multi-user multi-path space-time channel estimates. DOA estimation for each path is further carried out by using the extracted spatial signature vector. Aside from the simplicity in computation, the proposed DOA estimation method can effectively resolve multi-paths regardless of the correlation and DOA separations of the multi-paths